An analysis of solar radio burst types III and IV with relation to solar activities and geomagnetic storm / Nabilah Ramli - Nabilah , Ramli (2018)
Solar activities are natural phenomena that occur at the solar surface by ejecting energy into interplanetary space and consequently hitting Earth’s atmosphere where the commencement of geomagnetic storms. Generally, solar radio bursts originated at the same level as the solar flares, Coronal Mass Ejections (CMEs) and shock at solar atmosphere which the Sun project the radio energy into the interstellar medium. This is a novel study to investigate the correlation between solar burst type IV and type III based on their properties. The analysis is based on the statistical data of type IV and type III solar bursts from 2006 – 2011 and 10 selected events over 2006-2015. The statistics of solar burst type IV associated with type III were obtained through e-Callisto (Compact Astronomical Low-frequency Low-cost Instrument for Spectroscopy Transportable Observatory) Spectrometer in the years 2006 until 2011. The point of this examination is to discover whether type III bursts preserved energy to solar bursts type IV thus led to the formation of geomagnetic storm. Statistical data from this study showed that most of the burst type IV were preceded and followed by type III burst. The total number of type IV events studied was 37, with 20 preceded by type III and the remainder with other type. Predominantly, solar bursts events are accompanied with great solar flares (class X and M) producing major storms. Although the study did not show much correlation between bursts type IV and type III in producing these storms, there are several possible explanations from this result. It may be the case that solar events such as solar flare, CMEs and active region ejected from the solar disc is not heading towards Earth and the energy has eventually disperses into the interplanetary medium.